Theory of A-C circuits - Fich, Sylvan (Prentice-Hall, 1958)
Contents: 1. Basic Definitions and Concepts 2. Complex numbers and Phasor Algebra 3. Series and Parallel circuits 4. Resonance Phenomena 5. Network Analysis 6. Network Theorems and Treansformations 7. Magnetically coupled circuits 8. Polyphase circuits 9. Fouruer Analysis 10. The laplace Transformation 11. Elementary synthesis of two-terminal reactive networks from poles and zeros.